Korelasi Pemujaan Leluhur Dengan Fenomena Sampradaya Di Bali - Harsananda, Hari; Widyawati, Anak Agung Ayu Alit (PANGKAJA: JURNAL AGAMA HINDU, 2020)
Hinduism is a universal religion that has a variety of styles of worship of the Holy spirit which is called God. Variants embodied in this style of worship which have dichotomous implications, on the one hand provides freedom in terms of worship that is egalitarian, but on the other hand raises which debate is better so that friction tends to be unavoidable in this case. The conventional Balinese Hindu religion and Sampradaya actually have good values that can be offered, so that the transfer of beliefs internally in Hinduism is very possible. Another factor is the archaeic cultural style that is closely attached to the Balinese people who do have an agrarian system so that worship of God in its strength aspect is very foremosted and the boring religious style makes this variant of the internal transfer of faith a tantalizing thing. These factors further exacerbate the dispute between Sampradaya and the concept of local diversity in Bali. The solution to this friction is very necessary in order to maintain the stability of Hinduism in Bali in particular and Indonesia in general.